2020
DOI: 10.33438/ijdshs.736875
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on Anxiety States of Students in Faculty of Sport Sciences During COVID-19

Abstract: This study aims to investigate anxiety states of students in Faculty of Sport Sciences during coronavirus (Covid19) in terms of some variables. Total number of 166 students as 67 female and 99 male chosen by simple random sampling from Sinop University Faculty of Sport Sciences participated in this study. Informed consent form and Beck Anxiety Inventory were used as data collection tool. To disclose differences in statistical evaluation of the data Mann-Whitney U Test and for multiple comparisons Kruskal-Walli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 20 publications
0
8
0
3
Order By: Relevance
“…25 Covid-19'a yakalanma kaygısı ele alındığında da yine kadın sporcuların erkek sporculara kıyasla daha yüksek kaygı düzeyine sahip oldukları tespit edilmiştir. 39,[42][43][44] Bu ve benzeri sonuçların kadınların erkeklere kıyasla daha duygusal olmalarından kaynaklabileceği düşünülmektedir. Araştırma kapsamında ayrıca partneri olmayan sporcuların durumluk ve sürekli kaygı puanlarının, partneri olan sporculara kıyasla anlamlı biçimde daha yüksek olduğu saptanmıştır.…”
Section: Discussionunclassified
“…25 Covid-19'a yakalanma kaygısı ele alındığında da yine kadın sporcuların erkek sporculara kıyasla daha yüksek kaygı düzeyine sahip oldukları tespit edilmiştir. 39,[42][43][44] Bu ve benzeri sonuçların kadınların erkeklere kıyasla daha duygusal olmalarından kaynaklabileceği düşünülmektedir. Araştırma kapsamında ayrıca partneri olmayan sporcuların durumluk ve sürekli kaygı puanlarının, partneri olan sporculara kıyasla anlamlı biçimde daha yüksek olduğu saptanmıştır.…”
Section: Discussionunclassified
“…Şen & Kızılcalıoğlu concluded that students were dissatisfied with the distance learning process for reasons such as the boring courses in the distance learning method, the hindrance social life, and the lack of connection established with academicians [65]. Acar et al, examined the anxiety levels of sports science students during the Covid-19 pandemic and found that the students' anxiety levels were high [66].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some theories have examined the relationship between exercise and the reduction of psychological and mood symptoms. Among them are various psychological theories (such as psychological distraction, self-efficacy, and social interaction) and biochemical theories (such as the body's reactions to physical activity and the secretion of hormones serotonin and endorphins) (9).…”
Section: Dear Editormentioning
confidence: 99%